Toll-like receptor 7 agonists are potent and rapid bronchodilators in guinea pigs - Kaufman, Elad H. (2010)
BACKGROUND: Respiratory tract viral infections result in asthma exacerbations. Toll-like receptor (TLR) 7 is a receptor for viral single-stranded RNA and is expressed at high levels in the lungs. OBJECTIVE: Because TLR7 polymorphisms are associated with asthma, we examined the effects of TLR7 agonists in guinea pig airways. METHODS: We induced bronchoconstriction in guinea pigs in vivo by means of electrical stimulation of the vagus nerve or intravenous administration of acetylcholine and measured the effect of a TLR7 agonist administered intravenously. We induced contraction of airway smooth muscle in segments of isolated guinea pig tracheas in vitro and measured the effect of TLR7 agonists, antagonists, and pharmacologic inhibitors of associated signaling pathways administered directly to the bath. RESULTS: TLR7 agonists acutely inhibited bronchoconstriction in vivo and relaxed contraction of airway smooth muscle in vitro within minutes of administration. Airway relaxation induced by the TLR7 agonist R837 (imiquimod) was partially blocked with a TLR7 antagonist and was also blocked by inhibitors of large-conductance, calcium-activated potassium channels; prostaglandin synthesis; and nitric oxide generation. Another TLR7 agonist, 21-mer single-stranded phosphorothioated polyuridylic acid (PolyUs), mediated relaxation that was completely blocked by a TLR7 antagonist. CONCLUSIONS: These data demonstrate a novel protective mechanism to limit bronchoconstriction and maintain airflow during respiratory tract viral infections. The fast time frame is inconsistent with canonical TLR7 signaling. R837 mediates bronchodilation by means of TLR7-dependent and TLR7-independent mechanisms, whereas PolyUs does so through only the TLR7-dependent mechanism. TLR7-independent mechanisms involve prostaglandins and large-conductance, calcium-activated potassium channels, whereas TLR7-dependent mechanisms involve nitric oxide. TLR7 is an attractive therapeutic target for its ability to reverse bronchoconstriction within minutes.